The Paradox Of Consumer Protection In Indonesia: A Juridical And Policy Analysis On The Ineffectiveness Of Consumer Rights Enforcement - Masrukhin Masrukhin; Evi Ariyani; Leila Farouk (Faculty of Law, Universitas Pekalongan, 2025)
This study examines the factors that contribute to the failure of consumer protection policies in Indonesia. Indonesia's significant potential as a country with a large population and relatively high economic growth, making it crucial for this study to be inundated with imported goods. This study uses a qualitative approach with secondary data analysis from various sources. Secondary data were obtained from academic literature and government policies. The results of the study indicate that the factors contributing to the failure of consumer protection policies stem from legal, economic, and political aspects. The implementation of fair and firm consumer protection laws, and the government providing balanced protection to consumers and businesses, are key factors in the success of consumer protection policies. Strengthening dispute resolution institutions and product distribution supervisory institutions in the market also contribute significantly. Furthermore, the government needs to side with domestic products by restricting the flow of imports of foreign products. The conclusion of this study emphasizes the need for collaboration between the government, businesses, and consumers to create an ecosystem that supports fair consumer protection policies. The proposed recommendation to relevant parties is to urge legislative institutions to amend norms that weaken consumer rights in the Consumer Protection Law. It is hoped that these steps will have a positive impact on consumers, business actors and the national economy as a whole